The Effect of Problem-Based Learning Assisted by Monopoly Media on IPAS Learning Outcomes and Students’ Critical Thinking Ability - Mira Ariyani Safitri; Singgih Bektiarso; Iwan Wicaksono (Journal of Educational Studies, 2026)
This study investigated the effect of a Problem-Based Learning (PBL) model assisted by Monopoly media on IPAS learning outcomes and critical thinking skills among fourth-grade elementary school students. The study responds to the persistent challenge of low learning achievement and limited critical thinking resulting from teacher-centered instructional practices. The novelty of this research lies in the integration of PBL with Monopoly-based educational media to create a contextual and engaging learning environment in IPAS instruction. A quantitative approach with a posttest-only control group experimental design was employed. The study was conducted during the second semester of the 2025/2026 academic year at SDN 2 Alasmalang and SDN 1 Benelan Kidul, Banyuwangi Regency. The sample consisted of 47 fourth-grade students, including 24 students in the experimental group and 23 students in the control group. The experimental group received PBL instruction supported by Monopoly media, while the control group received conventional instruction. Data were collected through tests, observation, and documentation. Learning outcomes were measured using multiple-choice tests, whereas critical thinking skills were assessed through essay tests covering interpretation, analysis, evaluation, inference, explanation, and self-regulation. Data were analyzed using normality and homogeneity tests followed by independent-samples t-tests. The findings revealed that the PBL model assisted by Monopoly media significantly improved IPAS learning outcomes (p = 0.006) and critical thinking skills (p = 0.009). These results suggest that integrating PBL with Monopoly media is an effective instructional strategy for promoting meaningful learning and enhancing higher-order thinking skills in elementary IPAS education.